MICROBIAL QUALITY ASSESSMENT OF SLICED PINEAPPLE AND WATERMELON SOLD IN SOME SELECTED MARKETS IN KADUNA METROPOLIS, KADUNA STATE. - Madinatu B, Auta K. I.,; H. C, Yayock; B, Solomon (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2017)
Spoilage of fruits which results from the contamination by microorganisms into fruits through irrigation water, harvesting/processing equipment, improper storage, packaging and transporting, personal handling, soil, dust and even manure is a source of concern to human existence. To assess their microbial quality, sliced fruits sold at some selected markets within Kaduna metropolis were analyzed to determine the microorganism associated with the contamination. The bacterial mean counts in all the markets for Pineapple and Watermelon ranges between 1.5 x 105 – 9.5 x105 , and 1.4 x 105 – 9.9 x 105 respectively. The fungal mean count of pineapple and watermelon in the markets ranges from 1.0 x 105 – 1.2 x 105 and 1.1 x 105 – 2.0 x 105 respectively. The bacterial isolates were Staphylococcus spp, Escherichia coli, bacillus spp. While the fungal isolates includes, Aspergillus spp, penicillum, Rhizopus, Fusarium and yeast. The result reveals that the above microorganisms are responsible for microbial contamination of the fruits sold in the selected markets within Kaduna Metropolis. This therefore calls for serious attention in creating awareness in the control of human infectious diseases associated with consumption of contaminated raw fruits within the metropolis.